Literatur Review: Implementasi Pembelajaran Sosiokultural Berbasis Budaya Lokal Makassar dalam Pembentukan Karakter Anak Usia Dini - Asa Utami Sallewatang; Nabila Mahdia; Miftahurrahma Kaharuddin; Hajerah Hajerah; Muhammad Akil Musi (Ihya Ulum: Early Childhood Education Journal, 2026)
This study aims to analyze the implementation of sociocultural learning based on Makassar local culture in shaping early childhood character in the era of digital disruption. Using a literature review method with a qualitative descriptive approach, secondary data from 10 reputable scientific articles published between 2020 and 2026 were selected through four stages of systematic screening and analyzed using content analysis techniques. The findings indicate that the internalization of the philosophical values of Sipakatau, Sipakalebbi, Sipakainge’, and Siri’ na Pacce effectively shapes children’s moral-affective character through teacher modeling, the modification of traditional games such as Ma’bom, oral literature such as pappaseng, and regional language stimulation. The novelty of this study lies in the integration of Lev Vygotsky’s sociocultural theory with the reconstruction of Makassar local wisdom values as cyber-mediated cultural tools. The contribution of this study is the provision of a conceptual roadmap for strengthening partnerships among the three centers of education through the formulation of local culture-based digital parenting to mitigate the risks of virtual isolation and cultural alienation among Generation Alpha. The policy implications urge early childhood education administrators to integrate cultural matrices into the teaching modules of the Kurikulum Merdeka and require parents to apply active mediation in children’s gadget use through screen-time boundaries within the family environment